Advancing the Production of Transparent Solid Soaps with Indonesian Natural Oils - Zunita, Megawati; Yazid Bindar; Elvi Restiawaty; Syafira Pramesti; Mira Hayati (JURNAL QUIMICA, 2025)
Soap is created by combining sodium or potassium bases with fatty acids derived from vegetable or animal fats. Commonly used fats in soap production include palm oil, coconut oil, soybean oil, and peanut oil. The characteristics of the fatty acid or oil, along with the proportions of caustic soda (NaOH or KOH) and water, play a crucial role in determining the quality of the soap. Transparent soap is a solid soap in the shape of a bar that becomes see-through after the addition of a transparent component. This study developed soap by blending natural oils from Indonesia (coconut oil, palm oil, and nyamplung oil (Calophyllum Inophyllum). In addition, glycerine and a granulated sugar solution were added to the soap. Several tests are used to characterize the soap's properties, such as transparency, water content, foam stability, and hardness. According to the test results, the most clear oil is a blend of 60% palm oil, 25% coconut oil, and 15% nyamplung oil, with a sugar-to-glycerine ratio of 1:1. The soap does not satisfy the acceptable standards due to its high water content. Palm oil soap contains the least amount of water, with a sugar-to-glycerine ratio of 3:1 and a water content of 30%. Coconut oil is noted for its stable foam and high hardness. The characteristics and weight of soap are what determine its quality. Palm oil in various ratios, such as 2:1, 1:2, and 1:3, combined with a blend of other oils, can produce a high-quality transparent soap that fits specified requirements